2018
DOI: 10.3892/or.2018.6722
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑495 regulates human gastric cancer cell apoptosis and migration through Akt and mTOR signaling

Abstract: In the present study, we investigated the expression and cellular distribution of in human gastric cancer. Prominent downregulation of miR-495 activation was evident in patients with gastric cancer. Cell viability and Annexin V/PI apoptosis assays were used to assess cell proliferation and apoptosis. Then, western blot analysis was used to assess cyclin D1, PI3K, p-Akt and p-mTOR protein expression. Overexpression of miR-495 significantly inhibited cell proliferation, and promoted cell apoptosis of gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…21 The PI3K-AKT pathway, which is widely known as an important intracellular signalling pathway, plays a dominant role in apoptosis and proliferation of tumour cells by regulating the activation of downstream targets. 22,23 Precisely, the PI3K-AKT pathway has been shown to correlate with the genesis and progression of tumours as well as aggressive biological behaviours. In a previous study of colon cancer, WDR5 was found to be closely related to the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…21 The PI3K-AKT pathway, which is widely known as an important intracellular signalling pathway, plays a dominant role in apoptosis and proliferation of tumour cells by regulating the activation of downstream targets. 22,23 Precisely, the PI3K-AKT pathway has been shown to correlate with the genesis and progression of tumours as well as aggressive biological behaviours. In a previous study of colon cancer, WDR5 was found to be closely related to the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-345 could attenuate migration and the stem-like cell phenotype via inactivation of Rac1 by down-regulating EPS8 in GC (88). Overexpression of miR-495 suppressed cell proliferation and migration of GC, which could promote caspase-3/-9 and Bax protein expression and suppress cyclin D1 protein expression and the PI3K/Akt/mTOR pathway (89). In addition, overexpression of miR-375 attenuated the AKT/mammalian target…”
Section: Oncogenesis and Development Of Gastric Cancer And Mirnasmentioning
confidence: 99%
“…These studies have explored the possibility of using an appropriate drug delivery system to target and deliver miR-34a specifically to breast cancer cells, thereby enhancing its therapeutic effects. miR-34a is also a regulator of RTKs by affecting MET gene expression and plays a role in gastric cancer proliferation and metastasis [ 35 , 47 , 48 ]. Furthermore, miR-34a regulates downstream signaling pathways such as PI3K/Akt and Wnt/β-catenin [ 49 , 50 ].…”
Section: Small Non-coding Rtk-rnasmentioning
confidence: 99%
“…Such a pattern of alteration has also been implicated in lung squamous cell carcinoma [ 76 ]. miR-495 is also another regulator of cellular apoptosis and migration through modulation of the Akt/mTOR pathway and ErbB2 expression [ 47 , 48 ]. On the other hand, miR-206 mediates the regulation of c-MET, IGF1R, and MAPK3’s expression in gastric cancer.…”
Section: Small Non-coding Rtk-rnasmentioning
confidence: 99%